Enduring neurological sequelae of benzodiazepine use: an Internet survey - Christy Huff; A. J. Reid Finlayson; D. E. Foster; Peter R. Martin (SAGE Publishing, 2023)
Introduction: Benzodiazepine tapering and cessation has been associated with diverse symptom constellations of varying duration. Although described in the literature decades ago, the mechanistic underpinnings of enduring symptoms that can last months or years have not yet been elucidated. Objective: This secondary analysis of the results from an Internet survey sought to better understand the acute and protracted withdrawal symptoms associated with benzodiazepine use and discontinuation. Methods: An online survey ( n  = 1207) was used to gather information about benzodiazepine use, including withdrawal syndrome and protracted symptoms. Results: The mean number of withdrawal symptoms reported by a respondent in this survey was 15 out of 23 symptoms. Six percent of respondents reported having all 23 listed symptoms. A cluster of least-frequently reported symptoms (whole-body trembling, hallucinations, seizures) were also the symptoms most frequently reported as lasting only days or weeks, that is, short-duration symptoms. Symptoms of nervousness/anxiety/fear, sleep disturbances, low energy, and difficulty focusing/distractedness were experienced by the majority of respondents (⩾85%) and, along with memory loss, were the symptoms of longest duration. Prolonged symptoms of anxiety and insomnia occurred in many who have discontinued benzodiazepines, including over 50% who were not originally prescribed benzodiazepines for that indication. It remains unclear if these symptoms might be caused by neuroadaptive and/or neurotoxic changes induced by benzodiazepine exposure. In this way, benzodiazepine withdrawal may have acute and long-term symptoms attributable to different underlying mechanisms, which is the case with alcohol withdrawal. Conclusions: These findings tentatively support the notion that symptoms which are acute but transient during benzodiazepine tapering and discontinuation may be distinct in their nature and duration from the enduring symptoms experienced by many benzodiazepine users.